Modelo de eficiencia energética, como estrategia de negocio en la administración de la Planta Holcim-Latacunga - Willian Patricio, Maigua Valenzuela (2023)
Energy is an essential input in the production of cement, each process that integrates its manufacture uses energy inputs, therefore, energy efficiency can become a business strategy. In this sense, the work has as objective the development of an energy efficiency model as a business strategy in the administration of the Holcim plant to improve the operability and economic savings; For this, the work used applied research, seeking to solve a problem and provide innovative solutions to energy issues that affect the administration; In addition, the methodology had a mixed approach; qualitative and quantitative by using the criteria of the workers; through research instruments, to validate their knowledge and technical training regarding energy management as a business strategy. The results show that, in general, the plant complies with an average percentage of 43.46%, the administrative specifications and business strategies with the correct use of energy proposed by the ISO 50001:2018 standard.